Determinan profitabilitas dengan inflasi sebagai variabel pemoderasi - Triana, Nita; Rofiuddin, Mohammad (Journal of Accounting and Digital Finance, 2023)
This research aims to analyze the effect of the MSME financing, capital adequacy ratio, non-performing financing, and net operating margin on profitability with inflation as moderating variable in islamic banking in indonesian. The population used is the monthly financial statements of Islamic commercial banks for the period 2017-2021. With the saturated sampling technique, the number of samples was determined to be 60 months. The data is managed using moderated regression analysis (MRA). The findings show that MSME financing has no effect on profitability and capital has no effect on profitability. However, financing risk has a positive effect on profitability and net operating margin has a positive effect on profitability. Meanwhile, on the moderating variable, inflation can moderate MSME financing towards profitability. However, inflation cannot moderate capital, financing risk, and net operating margin on profitability.